Polycystic ovarian syndrome: pathogenesis and management - Thiam, Coumba Aicha; Antoine, Malyn M. L. K.; Antoine-Frank, Chrystal D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Polycystic ovarian syndrome (PCOS) is an endocrine disorder that commonly affects women of reproductive age. Its prevalence varies quite significantly and its clinical presentation includes: reproductive, metabolic and psychological issues. PCOS develops due to a variety of factors some of which are not yet fully understood. Due to the complexity in the development and presentation of this condition, the management of PCOS in most instances is complicated and involves the combination of pharmacological, non-pharmacological and surgical interventions. This review discusses the pathogenesis and management of PCOS as means of providing information that would enhance understanding and control of this disease.